2014
DOI: 10.1063/1.4903369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper surface pre-treatment on the properties of CVD grown graphene

Abstract: Here, we report the synthesis of high quality monolayer graphene on the pre-treated copper (Cu) foil by chemical vapor deposition method. The pre-treatment process, which consists of pre-annealing in a hydrogen ambient, followed by diluted nitric acid etching of Cu foil, helps in removing impurities. These impurities include native copper oxide and rolling lines that act as a nucleation center for multilayer graphene. Raman mapping of our graphene grown on pre-treated Cu foil primarily consisted of ∼98% a mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…Among these various approaches in the CVD process, modifying the surface morphologies of catalytic growth substrates is considered one of the most viable approaches for obtaining high-quality graphene. Mechanical or chemical treatments are typically used in such approach which significantly reduces the impurities present in the metal catalysts, the major source of the nucleation center, leading to the improved carrier mobility [26][27][28][29][30][31][32]. In this work, we revisit the role of surface morphology of metal catalyst to the quality of CVD graphene using commercially available copper foil via simple chemical treatments and analyze the resulting physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Among these various approaches in the CVD process, modifying the surface morphologies of catalytic growth substrates is considered one of the most viable approaches for obtaining high-quality graphene. Mechanical or chemical treatments are typically used in such approach which significantly reduces the impurities present in the metal catalysts, the major source of the nucleation center, leading to the improved carrier mobility [26][27][28][29][30][31][32]. In this work, we revisit the role of surface morphology of metal catalyst to the quality of CVD graphene using commercially available copper foil via simple chemical treatments and analyze the resulting physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2), the sizes of observed graphene nanosheets (Figure 3a Raman spectroscopy is very informative and sensitive for studying carbon materials [36]. It provides a quick and facile identification of carbon materials [21,23,37,38], which is a significant method to identify graphene. As shown in Figure 4, three characteristic bands are observed in each Raman spectrum, including D band (approximate 1340 cm −1 ), G band (approximate 1580 cm −1 ) and 2D band (approximate 2660 cm −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…They synthesized high quality and uniform graphene on Cu by this method which can effectively reduce the impurities on Cu. Raman mapping results showed that 98.3% of the mapped area exhibited monolayer characteristics with I 2D /I G > 2 compared to 75% monolayer characteristics for that grown on untreated Cu foil [34]. Jeong H, et al used ammonium persulfate solution combined with gentle ultrasonication (100 W) to remove the impurities on copper foil.…”
Section: Introductionmentioning
confidence: 99%